Computer-Based Software for Grammar Test: What The Students Think about It? - Widyani Solihat; Ngadiso Ngadiso; Slamet Supriyadi (International Journal of Language Teaching and Education, 2018)
A test is conducted to know the students’ competencies toward the material that they have been learned. Making the test is not easy because the lecturers have to consider the material or skill which will be tested, in this case is grammar. The lecturers also must use the test media which is appropriate and interesting. Nowadays, the utilizing of technology in education context has increased, especially in conducting the test. The aim of this study is to show the students’ perception toward computer-based software for grammar test. The method used in this research is qualitative method with descriptive analysis design and also used quantitative method for questionnaire data. The participants were from 40 English department students in one of university in Serang. The data were collected from questionnaire and interview with some students. The result shows that almost all students give positive response and perception toward computer-based software for grammar test. The students become more interesting to do the grammar test with the computer-based software and they are facilitated in conducting the test because they get benefits from it.